Analytical simulation of mixed convective Williamson nanofluid flow above a stretched Riga plate considering viscous dissipation effects - Rehman, Ali; Khan, Dolat; İnç, Mustafa; Rezapour, Shahram (World Scientific Publ Co Pte Ltd, 2025)
This work examines, accounting for viscous dissipation, an analytical simulation of mixed convection heat transfers in a Williamson blood base nanofluid flow on a stretched Riga plate (RP). The Lorentz force, which influences fluid dynamics, is produced by the alternating magnetic fields that comprise the RP. The flow characteristics are further complicated by the blood base Williamson nanofluid's (WN) non-Newtonian behavior. The governing partial differential equations (PDEs) for momentum and energy are transformed into a set of nonlinear ordinary differential equations (NODEs) by similarity transformations. We solve these equations analytically using the homotopy analysis method (HAM). We investigate in detail how the temperature and velocity profiles (VPs) are affected by significant parameters as the Williamson parameter (WP), viscous dissipation, volume friction of nanoparticles, modified Hartmann number (MHN), heat generation parameter and Biot number (BN). The findings show that the thermal conductivity (TC) of nanoparticles is increased, improving the efficiency of heat transfer. Moreover, a Lorentz force generated by the RP considerably alters the temperature and flow fields. With regard to the design and optimization of thermal systems utilizing complex boundary conditions (BCs) and non-Newtonian nanofluids, this work offers significant new insights.
Keywords: Williamson nanofluid; Riga plate; mixed convective; homotopy analysis method; viscous dissipation